Pembangunan Aplikasi Deportes Fitness - Masarudin, Muhammad Hairil Ikhwan; Saaidin, Muhammad Fikri; Mohd Radhi, Mohammad Amirul Haziq; Mohamed, Juliana (Multidisciplinary Applied Research and Innovation, 2023)
Since the advent of the Covid-19 pandemic, many people have stopped their exercise activities to stay fit. This is due to the fact that all exercise facilities, such as gyms, have been closed as it will pose a risk to the individual. The objective of the implementation of this project is to reduce the constraints to attend the gymnasium and help individuals, especially those who are new to fitness or sports activities on a daily basis. Deportes Fitness App was developed using mediated reality (AR) technology. The application provides information on sports, fitness and equipment in the gym, including making it easier for users to use. In addition, this application has information and information that helps those who want to use sports equipment such as dumbbells, treadmills, and other similar items in a safe way and effective..The method we use while running this application is to use the ADDIE model